Exploiting powder x-ray diffraction to establish the solvent-assisted solid-state supramolecular assembly of pillar[5]quinone - Shivakumar, Kilingaru I.; Yan, Yuncheng; Hughes, Colan E.; Apperley, David C.; Harris, Kenneth D. M.; Sanjayan, Gangadhar J. (Crystal Growth & Design, 2015)
We report the solvent-mediated supramolecular assembly of pillar[5]quinone (P[5]Q), a symmetric cyclamer containing five benzoquinone moieties bridged by five alternating methylene units. The supramolecular assembly of P[5]Q is shown to be facilitated by 1,1,2,2-tetrachloroethane (TCE) as solvent, producing a microcrystalline solvate material P[5]Q(.)2TCE with a fluffy texture. Optical and electron microscopy reveal that this material has a rod-shaped morphology, extending to several micrometers in length. Due to the microcrystalline nature of the material, structure determination was carried out directly from powder X-ray diffraction data, augmented by high-resolution solid-state C-13 NMR. The two crystallographically distinct TCE molecules occupy different types of void in the structure and have different dynamic properties. Crystallization of P[5]Q was attempted from a large number of different solvents, but only TCE was found to facilitate the formation of a crystalline phase. Indeed, features of the crystal structure suggest that the TCE component plays an important role in promoting the columnar assembly of P[5]Q molecules.